Novel nanofibrous sorbents for the extraction and determination of resveratrol in wine - Háková, Martina; Havlíková, Lucie Chocholoušová; Švec, František; Solich, Petr; Erben, Jakub; Chvojka, Jiří; Šatínský, Dalibor (Talanta, 2020)
On-line SPE HPLC method using nanofibrous sorbents for the extraction and determination of resveratrol in wine was developed and validated. Different types of nanofibrous and microfibrous polymers were tested and compared with commercial monolithic C18 sorbent. Polyamide and polyacrylonitrile nanofibers and composite materials composed of respective polycaprolactone and poly(vinylidene difluoride) nanofibers at microfibrous scaffold were included among tested materials. Two different polycaprolactone-based materials were prepared and their effect on the extraction properties studied. Alternatively, dopamine-coated polycaprolactone fibers were also used. Poly(vinylidene difluoride) nanofibers/polycaprolactone microfibers composite was found as the most effective sorbent and utilized for the method validation. Resveratrol in red wine was determined using our validated on-line SPE HPLC method.
Keywords: dopamin; Nanofiber polymers; víno; Resveratrol; resveratrol; Coating; Chromatography, High Pressure Liquid; On-line solid phase extraction; Red wine; vysokoúčinná kapalinová chromatografie; Polymers; extrakce na pevné fázi; Wine; nanovlákna; Dopamine; Nanofibers; Chromatography; polymery; Solid Phase Extraction